2017
DOI: 10.3892/mmr.2017.6164
|View full text |Cite
|
Sign up to set email alerts
|

The tripartite motif-containing protein 3 on the proliferation and cytokine secretion of rheumatoid arthritis fibroblast-like synoviocytes

Abstract: Recent studies have revealed fibroblast-like synoviocytes (FLS) as a pivotal effector cell in the inflamed joint of rheumatoid arthritis (RA) patients. FLS exhibit high proliferation rates and constitutive expression of cytokines, contributing to the pathogenesis of RA. In this study, we found that the expression of tripartite motif-containing protein 3 (TRIM3), a candidate tumor suppressor gene, was lower in synovial tissue samples of RA patients than in that of healthy controls. We then investigated the role… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 22 publications
1
18
0
1
Order By: Relevance
“…Our previous study has showed that TRIM3 is downregulated in RA synovial tissue samples and that TRIM3 overexpression inhibits the proliferation of RA FLS (M. Wang et al, ). Here, we showed that the expression of Foxo3a and TRIM3 in RA synovial tissues was significant lower than that in control tissues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous study has showed that TRIM3 is downregulated in RA synovial tissue samples and that TRIM3 overexpression inhibits the proliferation of RA FLS (M. Wang et al, ). Here, we showed that the expression of Foxo3a and TRIM3 in RA synovial tissues was significant lower than that in control tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Foxo3a and TRIM3 (M. Wang et al, 2017) expressing plasmids were used to transfect HEK293T packaging cells and lentiviral particles were harvested as previously described (M. Wang et al, 2017).…”
Section: Overexpression Of Foxo3a and Trim3mentioning
confidence: 99%
“…One gene is differentially expressed for the three comparisons, HLA-DPA1 gene. It is coding DP molecules which will confer, through their polymorphisms, a (Wang et al, 2017(Wang et al, , 2019. It is worth noting that TRIM3 is linked to FOXO3 (forkhead box O3, which belongs to the forkhead family of transcription factors), which is a gene of interest in Table S3 (q-value < 0.1).…”
Section: Discussionmentioning
confidence: 99%
“…the largest class of RING-finger E3 ligases in mammals. The TRIM proteins have been shown to be involved in a variety of biological processes including proliferation, apoptosis, and transcriptional regulation (22,23). It has been shown that TRIM3 is associated with the CART (cytoskeleton-associated recycling or transport) complex, which is necessary for efficient recycling of actin-dependent and constitutive plasma membrane receptors (24)(25)(26).…”
Section: Significancementioning
confidence: 99%